Psychological interventions as an alternative and add-on to antidepressant medication to prevent depressive relapse: systematic review and meta-analysis. (October 2021) - Breedvelt, Josefien Johanna Froukje; Brouwer, Maria Elisabeth; Harrer, Mathias; Semkovska, Maria; Ebert, David Daniel; Cuijpers, Pim; Bockting, Claudi Louisa Hermina
Abstract : Background: After remission, antidepressants are often taken long term to prevent depressive relapse or recurrence. Whether psychological interventions can be a viable alternative or addition to antidepressants remains unclear. Aims: To compare the effectiveness of psychological interventions as an alternative (including delivered when tapering antidepressants) or addition to antidepressants alone for preventing depressive relapse. Method: Embase, PubMed, the Cochrane Library and PsycINFO were searched from inception until 13 October 2019. Randomised controlled trials (RCTs) with previously depressed patients in (partial) remission where preventive psychological interventions with or without antidepressants (including tapering) were compared with antidepressant control were included. Data were extracted independently from published trials. A random-effects meta-analysis on time to relapse (hazard ratio, HR) and risk of relapse (risk ratio, RR) at the last point of follow-up was conducted. PROSPERO ID: CRD42017055301. Results: Among 11 included trials ( n = 1559), we did not observe an increased risk of relapse for participants receiving a psychological intervention while tapering antidepressants versus antidepressants alone (RR = 1.02, 95% CI 0.84–1.25; P = 0.85). Psychological interventions added to antidepressants significantly reduced the risk of relapse (RR = 0.85, 95% CI 0.74–0.97; P = 0.01) compared with antidepressants alone. Conclusions: This study found no evidence to suggest that adding a psychological intervention to tapering increases the risk of relapse when compared with antidepressants alone. Adding a psychological intervention to antidepressant use reduces relapse risk significantly versus antidepressants alone. As neither strategy is routinely implemented these findings are relevant for patients, clinicians and guideline developers.